Quality between the present and the future - Abdul Ghani Yousseph Kerm (University of Science and Technology, Yemen, 2008)
Quality between the present and the future abstract: This paper deals with some concepts related to the institution as well as some important international standards adopted in the evaluation and how the educational institution performance evaluation through implementation on the main elements of her to see the strengths and weaknesses then the adoption of some illustrative examples. Also this research pointing to some elements of the lecture successful and its role in the preparation of graduates distinct and active in the community as well as the role of human and physical planning, monitoring and ambitious and will tip the logic of reason to emotion in the advancement of the institution to live up to their counterparts in developed countries element. So that, they are able to fulfill the obligations of the needs and challenges of the next phase, and it comes to creativity, where is the option that makes a distinction between communities a way to stay in the powerful world.